Building a sustainable pop-up coffee shop; case study of rehat coffee - Maspul, Kurniawan Arif (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
Begin a riveting trip through the revolutionary leaps of Rehat Coffee, a dynamic pop-up coffee shop located in Banjarmasin, Indonesia. Rehat Coffee is pioneering a vibrant modern economic community by seamlessly combining features of the low-cost entrepreneurship, sustainability, and cultural heritage. Rehat Coffee expertly integrates global coffee trends and local preferences through thorough market research, smart collaborations, and environmentally conscientious procedures. This qualitative report thoroughly explores Rehat Coffee's strategic prowess and revolutionary impact on the econoociety, and environment. It'll be interesting to delve into Rehat Coffee's historical narrative, sustainability efforts, and community engagement to discover the tremendous potential of transforming the coffee landscape while encouraging long-term community development. The study sheds the spotlight on the consequences of Rehat Coffee's creative strategy for future entrepreneurs trying to balance profitability and sustainability, thereby motivating a new wave of socially responsible bmy, susiness practices.